Charge density studies of 3d metal (Ni/Cu) complexes with a non‐innocent ligand. Issue 4 (1st August 2017) - Chuang, Yu-Chun; Sheu, Chou-Fu; Lee, Gene-Hsiang; Chen, Yu-Sheng; Wang, Yu
Abstract : The redox characteristics of pairs of square planar complexes M (mnt)2 2− / M (mnt)2 −, where mnt is the non‐innocent maleonitriledithiolate ligand, are established through charge density analysis and X‐ray absorption spectroscopy: the oxidation is ligand based in Ni complexes and are metal based for the Cu case. Abstract : High‐resolution X‐ray diffraction experiments and atom‐specific X‐ray absorption experiments are applied to investigate a series of square planar complexes with the non‐innocent ligand of maleonitriledithiolate (mnt), [S2 C2 (CN)2 ] z −, containing M —S bonds. Four complexes of (PyH) z [ M (mnt)2 ] z −, where M = Ni or Cu, z = 2 or 1 and PyH + = C5 NH6 +, were studied in order to clarify whether such one‐electron oxidation–reduction, [ M (mnt)2 ] 2− /[ M (mnt)2 ] 1−, is taking place at the metal or the ligand site. Combining the techniques of metal K ‐, L ‐edge and S K ‐edge X‐ray absorption spectroscopy with high‐resolution X‐ray charge density studies, it is unambiguously demonstrated that the electron redox reaction is ligand based and metal based for Ni and Cu pairs, respectively. The bonding characters in terms of topological properties associated with the bond critical points are compared between the oxidized form [ ML ] − and the reduced form [ ML ] 2− . In the case of Ni complexes, the formal oxidation state of Ni remains as Ni 2+ and each mnt ligand carries a 2− charge in [Ni(mnt)2 ] 2−, but only one of the ligands is formally oxidized in [Ni(mnt)2 ] 1− . In contrast, in the case of Cu complexes, the mnt remains as 2− in both complexes, but the formal oxidation states of the metal are Cu 2+ and Cu 3+ . Bond characterizations and d ‐orbital populations will be presented. The complementary results of XAS, XRD and DFT calculations will be discussed. The conclusion on the redox reactions in these complexes can be firmly established.